2016
DOI: 10.1523/jneurosci.0709-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Neural Basis of Acquired Amusia and Its Recovery after Stroke

Abstract: Although acquired amusia is a relatively common disorder after stroke, its precise neuroanatomical basis is still unknown. To evaluate which brain regions form the neural substrate for acquired amusia and its recovery, we performed a voxel-based lesion-symptom mapping (VLSM) and morphometry (VBM) study with 77 human stroke subjects. Structural MRIs were acquired at acute and 6 month poststroke stages. Amusia and aphasia were behaviorally assessed at acute and 3 month poststroke stages using the Scale and Rhyth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
71
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(84 citation statements)
references
References 73 publications
12
71
1
Order By: Relevance
“…Using both the replication cohort ( N = 43; see Supplementary Material) and the larger pooled sample ( N = 90) of stroke patients, we were able to ascertain our previous results (Sihvonen et al, 2016) that (i) acquired amusia was associated with an acute stage lesion pattern in right temporal, insular, and striatal areas and that (ii) non-recovered amusia was linked to longitudinal GMV decrease in right temporal areas, located posteriorly for pitch amusia and more anteriorly for rhythm amusia. Importantly, compared to the previous study, the larger pooled sample also enabled us to carry out direct lesion comparisons to evaluate lesion patterns associated with amusia recovery.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Using both the replication cohort ( N = 43; see Supplementary Material) and the larger pooled sample ( N = 90) of stroke patients, we were able to ascertain our previous results (Sihvonen et al, 2016) that (i) acquired amusia was associated with an acute stage lesion pattern in right temporal, insular, and striatal areas and that (ii) non-recovered amusia was linked to longitudinal GMV decrease in right temporal areas, located posteriorly for pitch amusia and more anteriorly for rhythm amusia. Importantly, compared to the previous study, the larger pooled sample also enabled us to carry out direct lesion comparisons to evaluate lesion patterns associated with amusia recovery.…”
Section: Discussionmentioning
confidence: 79%
“…Recently, we utilized VLSM in a sample of 77 stroke patients from two Finnish cohorts (from Helsinki and Turku) to map the lesioned brain regions specifically associated with acquired amusia (Sihvonen et al, 2016). The results revealed that damage to the right STG, middle temporal gyrus (MTG), insula, and putamen form the crucial neural substrate for acquired amusia.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, cross-sectional studies have associated musical training and aural skills with greater gray matter volume and its myelination in several brain regions including the insular cortices Shimizu and Sakai, 2015]. Lesions of the insula and its disconnection with the auditory cortex have furthermore been associated with musical anhedonia [Satoh et al, 2005;Sihvonen et al, 2016], whereas positive responses to pleasurable music correlated with enhanced activity in frontoinsular areas in trained musicians [Brattico et al, 2015]. This is in line with a prominent theory that features the insula as the neural substrate of human awareness [Craig, 2002[Craig, , 2009a[Craig, , 2011.…”
Section: Introductionmentioning
confidence: 99%
“…These deficits are all common after stroke, with an estimated incidence of around 30% for aphasia, 35–69% for amusia, and 20–50% for memory deficits . Although aphasia and amusia can occur separately, there is clear comorbidity between the disorders after stroke, with 40–50% of amusic persons also having at least mild aphasia . Although aphasia and amusia are naturally associated with impaired processing of speech and musical melodies, respectively, the neural processing of vocal music (songs) seems to be relatively well preserved in these conditions after stroke .…”
Section: Introductionmentioning
confidence: 99%
“…35,36 Although aphasia and amusia can occur separately, there is clear comorbidity between the disorders after stroke, with 40-50% of amusic persons also having at least mild aphasia. 34,37,38 Although aphasia and amusia are naturally associated with impaired processing of speech and musical melodies, respectively, the neural processing of vocal music (songs) seems to be relatively well preserved in these conditions after stroke. 39 Moreover, as dysfunctions in the left and right frontotemporal networks are the key underlying cause of aphasia [40][41][42] and amusia, 37,43,44 respectively, the wide-scale and largely bilateral composition of the temporal, frontal, and limbic networks involved in the processing of songs [45][46][47] could potentially make them effective in both aphasia and amusia.…”
Section: Introductionmentioning
confidence: 99%